2018
DOI: 10.12678/1089-313x.22.3.142
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fatigue on Star Excursion Balance Test Performance in Dancers

Abstract: Dance is associated with a high risk of injury and fatigue is often a contributing factor. The Star Excursion Balance Test (SEBT) has been used to identify alterations in normal movement that may contribute to injury risk; however, there has been limited investigation of the potential effects of fatigue. The aim of this study was to explore the influence of dance-specific fatigue on SEBT performance, with implications for injury and performance in dance. Thirty-five university dancers completed the modified SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 33 publications
6
31
1
Order By: Relevance
“…An interesting result is that the PL reach distance increased by 2.17% post fatigue in the non-dominant leg ( Table 5). Similar results were reported by Armstrong et al [42] when examining the effect of fatigue on SEBT performance among university dancers. According to the authors, the increased reach distance might be related to the distinct characteristics of the dance sport as the dancers may have distinct and variable kinematic strategies to maintain or facilitate the SEBT performance under the fatigued condition [42].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…An interesting result is that the PL reach distance increased by 2.17% post fatigue in the non-dominant leg ( Table 5). Similar results were reported by Armstrong et al [42] when examining the effect of fatigue on SEBT performance among university dancers. According to the authors, the increased reach distance might be related to the distinct characteristics of the dance sport as the dancers may have distinct and variable kinematic strategies to maintain or facilitate the SEBT performance under the fatigued condition [42].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the PM reach distance significantly decreased post fatigue only when using the dominant leg for support (Table 3), which also supported this view. Previous findings have indicated that the reach distances in SEBT were associated with the kinematics [42] and kinetics [43,44] of the supporting leg. Therefore, the greater decrement of reach distance post fatigue when using the dominant leg for support may indicate a higher fatigue rate in the dominant leg.…”
Section: Discussionmentioning
confidence: 91%
“…An interesting result is that the PL reach distance increased by 2.17% post fatigue in the non-dominant leg. Similar results were reported by Armstrong et al [41] when examining the effect of fatigue on SEBT performance among university dancers. According to the authors, the increased reach distance might be related to the distinct characteristics of the dance sport as the dancers may have distinct and variable kinematic strategies to maintain or even facilitate the SEBT performance under the fatigued condition [41].…”
Section: Sebt Performancessupporting
confidence: 88%
“…Similar results were reported by Armstrong et al [41] when examining the effect of fatigue on SEBT performance among university dancers. According to the authors, the increased reach distance might be related to the distinct characteristics of the dance sport as the dancers may have distinct and variable kinematic strategies to maintain or even facilitate the SEBT performance under the fatigued condition [41]. In the present study, although the PL reach distance increased with fatigue (2.17%) in the nondominant leg, this data should be used with caution in practice, due to the SD (8.04%) was much higher than the mean.…”
Section: Sebt Performancessupporting
confidence: 88%
See 1 more Smart Citation